REDUKSI JUMLAH BIJI CABAI RAWIT (Capsicum frutescents) DENGAN MENGGUNAKAN SARI AKAR ECENG GONDOK (Eichhornia crassipes) - Ferdia Windarti; Tatang Sopandi (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2018)
Cayenne pepper is one of the important economic agricultural commodities and is widely used in the food industry. However, the presence of cayenne pepper seeds is not favored by some people because if consumed can cause digestive disorders. Giberelin is one of the growth regulating substances commonly used to produce seedless fruit growth. This study aims to explore the effect of water hyacinth root extract (Eichhornia crassipes) on plant height, yield and number of cayenne pepper seeds. The study was carried out experimentally using a completely randomized design (CRD) of 4 extract treatments, namely 0 g / l (control), 25 g / l, 50 g / l, and 75 g / l of water hyacinth root extract, each of which was repeated six times. The results of this study indicate that the provision of water hyacinth root extract can increase plant height and yield but reduce the amount of cayenne pepper seeds. The concentration of water hyacinth root extract 75 g / l is the best water hyacinth root extract that can produce an average plant height of 65.67cm, an average yield of 206.50 fruits per plant with an average fruit yield of 170.17 gram per plant and the average number of seeds is 31.17 seeds per cayenne pepper. This study concluded that the root extract of goiter water can reduce the number of seeds and increase plant height and yield of cayenne pepper. Keywords: cayenne pepper, giberelin hormone, water hyacinth and cayenne pepper seeds.